Vegetation-based slope protection using bermuda grass: Effects on the dynamic elastic modulus of weakly expansive soil - Xin Huang; Wei Zheng; Li-Dong Tang; Jian-Cai Xie; Chao Chen; Jing-Kai Wu; Hong-Wei Liu; Hui Xu (PLoS ONE, 2026)
Weakly expansive soil is utilized in subgrades and slope engineering. vegetation is commonly adopted for ecological reinforcement, and its effects on the dynamic mechanical behaviors of weakly expansive soil remain to be further studied. Effects of vegetation, dynamic stress amplitude, confining pressure, and loading frequency on the dynamic strain and dynamic elastic modulus of weakly expansive soil were analyzed in this study. Specifically, different planting densities of Bermuda grass were investigated, including 25 g/m², 40 g/m², 50 g/m², which are denoted as P25, P40 and P50 respectively. Test Results showed that 1) Bermuda grass effectively mitigated the cumulative dynamic strain. Specifically, at f = 1 Hz and σ d = 20 kPa, the cumulative dynamic strain of the P25, P40, and P50 groups decreased by 9.5%, 17.0%, and 19.7% compared with bare soil. 2) Bermuda grass weakened the effect of confining pressure on the dynamic elastic modulus of soil. when σ 3 increased from 50 kPa to 100 kPa, the dynamic elastic modulus of bare soil rose by 16.4%, while the increment of the P50 group was only 1.7%. 3) Bermuda grass also enhanced dynamic stiffness of weakly expansive soil, and the reinforcing effects presented a positive correlation with planting density. Under sinusoidal cyclic loading ( f = 1 Hz, σ d = 40 kPa), the dynamic elastic modulus of P25, P40 and P50 were 6.4%,12.8% and 26.16% higher than that those of soil, respectively. Overall, Bermuda grass substantially improves the dynamic deformation resistance and stiffness of weakly expansive soils, which indicates its strong potential for enhancing shear strength and structural stability in expansive soil engineering under dynamic loading.